Síntesis de Puntos Cuánticos de SnO2 por Precipitación Química Asistida con Radiación Ultrasónica - Alvarado y Cols., P. (2019)
SnO2 quantum dots were prepared via chemical precipitation assisted with ultrasonic waves. X-ray diffraction analysis (XRD) confirmed the tetragonal rutile structure of quantum dots SnO2 with crystallite size of 1.4 nm. The scanning electron microscopy (SEM) micrographs of the obtained powder sample show that the SnO2 quantum dots are agglomerated particles around 10 nm, while the transmission electron microscopy (TEM) images confirm that the crystallite size is similar to the measurement made by X-ray diffraction (XRD). The energy bandwidth of the quantum dots of SnO2 measured by UV Vis spectroscopy of diffuse reflection was 4.3 eV, showing a significant displacement attributed to the quantum confinement.